Comunidades profesionales de aprendizaje: de la gestión empresarial a la gestión educativa - Morales Inga, Sergio (2019)
Since the late 1980s, pedagogy has taken a paradigm shift. Once based on indi-vidualistic and hierarchical strategies, currently defends its reflective and colla-borative nature. Originated in business management, professional learning communities have shown a positive impact in educational management. Through an exhaustive literature review, this research synthesizes the theory of professional learning communities, analyzing their main components: flexible organizational structure, shared leadership, organizational values, shared vision and collaborative school culture. Finally, the research suggests that the development of organizational strategies focused on the school could complement the work carried out through educational policies.